Risk factors for contracting malaria in six wards of Mudzi District, Zimbabwe: A case control-study - Tichaona Fambirai; Moses J. Chimbari; Pisirai Ndarukwa (PLoS ONE, 2025)
Despite a significant decline in burden in the last two decades, malaria remains a significant global public health threat. Vector behaviour, climate, ecology, human economic and social behaviour, and quality of housing are some of the established predictors for contracting malaria. Zimbabwe has recorded a significant decline in malaria burden, however, districts like Mudzi continue to experience persistent malaria transmission despite well-performing indoor residual spraying programs. Persistent malaria transmission despite high IRS coverages point to human socio-economic behavior and health system factors, which have not been fully investigated. We therefore conducted this unmatched case-control study to identify human socio-economic, behavioural, and health system primary factors responsible for persistent malaria transmission in the district. We recruited 94 cases and 91 controls into the study. Cases were randomly recruited from health facility malaria treatment registers, whilst controls were neighbors of a case randomly recruited from a village household register. A case was defined as an individual residing in a selected village with a positive RDT test result. A control was an individual with no recorded positive RDT result recruited from the same village as a case. A structured questionnaire was used to collect data on socio-demographic characteristics of participants, behavior, perception of quality of health services, and knowledge on malaria causes, symptoms, and prevention. A key information guide was used to acquire perceptions of health managers on primary factors driving malaria in the district, as well as the performance of malaria control and treatment services. Kobo Collect was used for real-time data collection. Quantitative data were analyzed using STATA 13 (StataCorp LLC) to generate frequencies and odds ratios. Multivariate logistic regression analysis was conducted to identify independent risk factors for malaria. Independent risk factors for contracting malaria were: engaging in night outdoor social and religious activities (AOR = 8.13; 95% CI,1.74–37.90), and having a garden (AOR = 4.51; 95% CI,1.55–13.12). Wearing full body clothing at night (AOR = 0.13;95% CI,0.03–0.0.53), and sleeping in a sprayed room (AOR = 0.04; 95% CI,0.01–0.31) were protective for contracting malaria. The majority of cases (96.74%) and controls (92.22%) had good knowledge of malaria transmission and preventative measures. Despite high knowledge, outdoor religious activities and outdoor socialization were significantly associated with contracting malaria. Increased night outdoor activity increases the likelihood of vector-human contact away from IRS-protected spaces. Sustaining IRS and intensifying integrated, targeted community engagement and malaria awareness programs will be key in eliminating malaria in Mudzi.